2016
DOI: 10.1038/tpj.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine S-methyltransferase testing for averting drug toxicity: a meta-analysis of diagnostic test accuracy

Abstract: Thiopurine S-methyltransferase (TPMT) deficiency increases the risk of serious adverse events in persons receiving thiopurines. The objective was to synthesize reported sensitivity and specificity of TPMT phenotyping and genotyping using a latent class hierarchical summary receiver operating characteristic meta-analysis. In 27 studies, pooled sensitivity and specificity of phenotyping for deficient individuals was 75.9% (95% credible interval (CrI), 58.3-87.0%) and 98.9% (96.3-100%), respectively. For genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Sensitivity and specificity of phenotyping for deficient patients are 75.9% and 98.9%, respectively, and for TPMT*2 and TPMT*3 genotypes 90.4% and 100.0%, respectively. In cases with deficient or intermediate activity, phenotype sensitivity and specificity are 91.3% and 92.6%, respectively, and for TPMT*2 and TPMT*3 88.9% and 99.2%, respectively [145]. TPMT testing shows that approximately 90% of patients receiving thiopurines are wild-type and that nearly 30% of patients may benefit with TPMT testing and consequent dosing modification to reduce the incidence of myelosuppression [146].…”
Section: Bevacizumab and Paclitaxelmentioning
confidence: 99%
“…Sensitivity and specificity of phenotyping for deficient patients are 75.9% and 98.9%, respectively, and for TPMT*2 and TPMT*3 genotypes 90.4% and 100.0%, respectively. In cases with deficient or intermediate activity, phenotype sensitivity and specificity are 91.3% and 92.6%, respectively, and for TPMT*2 and TPMT*3 88.9% and 99.2%, respectively [145]. TPMT testing shows that approximately 90% of patients receiving thiopurines are wild-type and that nearly 30% of patients may benefit with TPMT testing and consequent dosing modification to reduce the incidence of myelosuppression [146].…”
Section: Bevacizumab and Paclitaxelmentioning
confidence: 99%
“…6-Thioguanine levels have been associated with thiopurine efficacy, while 6-MMP levels ARE associated with drug-related toxicity (190)(191)(192). Testing for TPMT activity has therefore been suggested to predict thiopurine toxicity, including bone marrow suppression (191,193,194), although with conflicting findings (195,196). The costeffectiveness of TPMT testing (197,198) needs to be re-evaluated (199)(200)(201)(202).…”
Section: Thiopurinesmentioning
confidence: 99%
“…Notably, TWAS also identified TPMT as a high confidence gene associated with IEAA and PhenoAge. TPMT ’s product, thiopurine S-methyltransferase (TPMT), metabolizes thiopurine immunosuppressants 46 . Little data is available on the endogenous function of TPMT; its role in metabolizing immunosuppressants and our PheWAS findings linking SNPs near TPMT to immune-related disorders like post-dysenteric arthropathy and Guillain-Barre syndrome suggest it may enhance immune activity, while our GO analysis suggested that it may be involved in metabolism, mitochondrial function, and cellular response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%